Desain Aplikasi Pengingat Interaktif untuk Orang dengan Penyakit Demensia Berbasis Mobile - Marcelino, I Dewa Made Candra Wiguna; Sanjaya ER, Ngurah Agus (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 12 No 2 (2023): JELIKU Volume 12 No 2, November 2023, 2023)
Every 3 seconds, 1 person in the world develops dementia. The worldwide incidence of Alzheimer's dementia is increasing rapidly and is currently estimated to approach 46.8 or 50 million people diagnosed with dementia in the world, 20.9 million in Asia Pacific, there are about 10 million new cases every year. In Indonesia itself, it is estimated that there were around 1.2 million people with dementia in 2016, which will increase to 2 million in 2030 and 4 million people in 2050.recommended. In order to help dementia patients and decrease the growth of dementia, author create a design solution using prototyping and UML methods. Using this prototype, user will be getting any reminder and other creative interactions. Hopefully this solution will helped indonesian people who have dementia and reduce the growth of dementia cases.